Complementary technologies, knowledge relatedness, and invention outcomes in high technology mergers and acquisitions - Makri, Marianna; Hitt, Michael A.; Lane, Peter J. (Strategic Management Journal, 2010)
Abstract Prior research on M&As and invention outcomes has not systematically examined the influence of two types of knowledge differences. Knowledge relatedness has typically been equated with knowledge similarity and the separate influence of knowledge complementarity has been overlooked. Similarly, studies examining innovation outcomes of M&As have typically focused on the role of technological knowledge and overlooked the influence of scientific knowledge. We develop a model of relatedness and invention performance of high‐technology M&As that considers science and technology similarity and complementarity as important drivers of invention. We test the model using a sample of M&As from the drug, chemical, and electronics industries and a fine‐grained measure of knowledge relatedness that distinguishes between science and technology relatedness. We find that complementary scientific knowledge and complementary technological knowledge both contribute to post‐merger invention performance by stimulating higher quality and more novel inventions. This suggests that high‐technology firms seeking acquisitions should search for, identify, and acquire businesses that have scientific and technological knowledge that is complementary to their own. Our results also suggest that similarities in knowledge facilitate incremental renewal, while complementarities would make discontinuous strategic transformations more likely, and that absorptive capacity research should be expanded to consider complementarities as well as similarities. Copyright © 2010 John Wiley & Sons, Ltd.